Utilizing Feedback: Helping Learners Make Sense of the Feedback They Get - Helen Barrett Fromme; Allison Hickey Mariani; Matthew Harris Zegarek; Sean Swearingen; Sarah-Anne Schumann; Michael S. Ryan; Shalini Reddy (Association of American Medical Colleges, 2015)
Abstract Introduction Many learners continue to report not getting adequate feedback in both quality and quantity. Although many workshops have been developed to train faculty and other educators in how to effectively give feedback in a clinical setting, there is only one MedEdPORTAL resource that targets how to solicit feedback from the learner perspective. Though the latter of these does address feedback solicitation, it does not address how learners can use that feedback. To address this issue, two authors of this resource conducted focus groups of students, residents, and faculty at three institutions across the nation to determine best practices for learners to ask for and utilize feedback most effectively. The qualitative data were analyzed and used in conjunction with a robust literature review to develop the two-module FAIR (Feedback: Asking, Implementing and Relaying) Curriculum. The second of these resources focuses on utilizing feedback, is presented here. Methods This module is a 1− to 1.25-hour module designed to teach learners how to understand and effectively utilize the feedback they receive from clinical teachers. It uses trigger tapes as well as audience reflection and participation to actively engage the learners throughout the workshop. This workshop is best used in sequence with the first workshop "Asking for Feedback: Helping Learners Get the Feedback They Deserve." The first should be offered at the beginning of the academic year, while this one should follow after 2-3 months of clinical experience. Results In 2013, the workshop was delivered to third-year medical students and first-year residents (internal medicine, pediatrics, family medicine) at three institutions: University of Chicago, Virginia Commonwealth University, and University of Oklahoma-Tulsa. We were able to obtain pre/post knowledge and attitude surveys of the learners at each workshop. The data suggest a trend towards higher knowledge of feedback solicitation and utilization skills, as well as appreciation for the importance of doing so. Additionally, we used historical control data to compare frequency of asking for and ability to utilize feedback. First-year residents did not show any significant differences, but students were significantly more likely to solicit feedback as the year progressed when they had taken the workshop. Discussion This module effectively ensures that the role of the learner is discussed during the dynamic and collaborative process of feedback between learners and educators. After positive feedback from both the residency programs and medical schools, we were invited to return for the second year to deliver the curriculum again. At one site, the curriculum is now an annual and expected part of the pediatric first-year resident and the third-year medical school curriculum.